Partnerships between a University-Affiliated Clinic and Community Based Organizations to Reach Black Men who have Sex with Men for PrEP Care. (4th October 2017) - Clement, Meredith; Okeke, Nwora Lance; Munn, Terry; Hunter, Miguel; Alexis, Kareem; Corneli, Amy; Sena, Arlene; McGee, Kara; McKellar, Mehri
Abstract: Background: While pre-exposure prophylaxis (PrEP) is a promising strategy for reducing HIV transmission, persons at highest risk for infection are not being adequately reached, particularly Black Men who have Sex with Men (MSM). Methods: In December 2015, a dedicated PrEP clinic was established at Duke University Medical Center in Durham, North Carolina (NC). We performed a retrospective review of patients evaluated at the PrEP clinic, abstracting the following routinely collected variables: age, race, ethnicity, sex at birth, self-identified gender, HIV risk factors and source of referral. Descriptive statistics are presented as medians and frequencies. Results: Over 18 months, 91 patients were evaluated. Most were male (90%, n = 82), approximately half were non-Hispanic Black (46%, n = 42), and median age was 31 years (range 19–66). Most patients identified as MSM (78%, n = 71) and 3 (3%) were transgender women who have sex with men (TGW). Specifically, 30% ( n = 27) were Black MSM or TGW. Risk factors for all patients included multiple sexual partners (65%), known HIV+ partner (19%), or a recent sexually transmitted infection (16%). One-quarter of patients ( n = 23) were uninsured. Among all Black patients, the most common source of referral was a community-based organization (CBO) (40%, n = 17), and specifically, Black MSM and TGW were most commonly referred by a CBO (44%, n = 12). Among White patients, most were self-referrals (47%, n = 18). Demographic characteristics of our patient population relative to those newly diagnosed with HIV in NC in 2015 are shown in Table 1. Conclusion: Although further efforts are needed to improve PrEP uptake in underserved populations in NC, the racial breakdown of our PrEP clinic is more representative of the national HIV epidemic as compared with all PrEP users in the US. Our study demonstrates that community partnerships can be a valuable avenue for patient recruitment and achieve success in reaching Black MSM with messages about PrEP. Disclosures: All authors: No reported disclosures.